Philosophy of experimental biology - Weber, Marcel (Cambridge studies in philosophy and biology., 2005)
"Philosophy of Experimental Biology explores some central philosophical issues concerning scientific research in modern experimental biology, including genetics, biochemistry, molecular biology, developmental biology, neurobiology, and microbiology. It seeks to make sense of the explanatory strategies, concepts, ways of reasoning, approaches to discovery and problem solving, tools, models, and experimental systems deployed by modern life science researchers and also integrates recent developments in historical scholarship, in particular the New Experimentalism.